Factors related to instrumental activities of daily living in persons with chronic thromboembolic pulmonary hypertension. (25th September 2021) - Iwasawa, Tatsuya; Fukui, Shogo; Kawakami, Michiyuki; Kawakami, Takashi; Kataoka, Masaharu; Yuasa, Shinsuke; Fukuda, Keiichi; Fujiwara, Toshiyuki; Tsuji, Tetsuya
Instrumental activities of daily living (IADL) are significantly related to quality of life and mortality among individuals with heart disease. However, few reports have examined IADL in persons with chronic thromboembolic pulmonary hypertension (CTEPH). The aim of this study was to clarify factors related to IADL in persons with CTEPH. This retrospective, observational study enrolled 163 persons with CTEPH (mean ± standard deviation age = 65 ± 13 years; 68% female) admitted to the Department of Cardiology at Keio University Hospital between January 2015 and July 2019. The Frenchay Activities Index (FAI) was used to assess IADL. Age, sex, body mass index, World Health Organization functional class (WHO-FC), cardiac function (mean pulmonary arterial pressure, mean right atrial pressure, pulmonary capillary wedge pressure, and cardiac index), pulmonary function (percentage vital capacity, percentage forced expiratory volume in 1 s, diffusion capacity of carbon monoxide (DLCO)/alveolar volume (VA)), physical function (knee extension strength and walking speed), and 6-min walking distance (6MWD) were assessed. Multiple regression analysis was performed to identify factors significantly associated with FAI. Mean FAI was 25 ± 8. Univariate analysis showed that sex, WHO-FC, DLCO/VA, walking speed, and 6MWD were correlated with FAI. Multiple regression analysis showed that 6MWD (sβ = 0.338, 95% CI 0.014–0.034, p < .001), sex (sβ = 0.268, 95% CI 2.238–7.165, p < .001), and DLCO/VA (sβ = 0.257, 95% CI 1.011–3.528, p < .001) were significantly correlated with FAI ( R 2 = 0.261). IADL were associated with exercise tolerance, sex, and DLCO/VA in persons with CTEPH. In the future, more details of IADL are expected to be clarified by analyzing individual components of IADL and investigating social background characteristics, including living environment.